ANALISIS HAMBATAN BELAJAR SISWA SMP DALAM MEMAHAMI KONSEP GARIS DAN SUDUT - Andrew Wantah; Hendri Prastyo (Jurnal Padegogik, 2022)
Lines and angles as one of the math topic which is beneficial in life is attainable at junior high school. The results of the given learning can be observed by their understanding skills. In gaining mastery of understanding concepts of lines and angles, everyone will face obstacles. The purpose of this research is to analyze students’ understanding skills and learning obstacles which is experienced by students on the topic of lines and angles. Learning obstacles included are ontogeny obstacles, didactical obstacles, and epistemological obstacles. In this research, with SMP Advent Ciracas as the research places with a total subject of 26 students,it is found that:(1)42.3% of students are capable of restating concepts, (2)0% of students are capable of giving examples of a concept completely, (3)46.2% of students are capable of representing concepts, (4)23.1% of students are capable clasifying objects based on math concepts, and (5)3.8% of students are capable of connecting math concepts internally or externally. The average score is 4.69, with the maximum score obtainable is 10. This shows that the understanding skills of students is considered weak. For that, analysis on learning obstacles which is the causative factor is done. By the result of research, learning obstacles are found. Epistemological obstacles found are: (1)students have difficulty in identifying point on a line; (2)students mistakes the concept of parallel lines and have limited concept of line segments; (3)students have difficulty on perpendicular position of two lines; (4)students have difficulty computing complementary angles. Didactical obstacles found are: (1)the given learning which doesn’t serve students in constructing their knowledge; (2)weak reinforcement on prerequisite subjects for lines and angles; (3)obstacles caused by inadequate facilities. Ontogeny obstacles found are: (1)students’ unpreparedness in studying online; (2)lack of mental strenghts for studying lines and angles.